Activated protein C decreases tumor necrosis factor related apoptosis-inducing ligand by an EPCR- independent mechanism involving Egr-1/Erk-1/2 activation - O'Brien, Lee A; Richardson, Mark A; Mehrbod, Sean F; Berg, David T; Gerlitz, Bruce; Gupta, Akanksha; Grinnell, Brian W (Arteriosclerosis, thrombosis, and vascular biology, 2007)
Background- APC is an antithrombotic and antiinflammatory serine protease that plays an important role in vascular function. We report that APC can suppress the proapoptotic mediator TRAIL in human umbilical vein endothelial cells, and we have investigated the signaling mechanism. APC inhibited endothelial TRAIL expression and secretion and its induction by cell activation. To explore the mechanism, we examined factors associated with TRAIL regulation and demonstrated that APC increased the level of EGR-1, a transcriptional factor known to suppress the TRAIL promoter. APC also induced a significant increase in phosphorylation of ERK-1/2, required to activate EGR-1 expression. Activation of ERK-1/2 was dependent on the protease activated receptor-1 (PAR-1), but independent of the endothelial protein C receptor (EPCR). Using siRNA, we found that the effect of APC on the EGR-1/ERK signaling required for TRAIL inhibition was dependent on the S1P1 receptor and S1P1 kinase. Our data suggest that APC may provide cytoprotective activity by activating the ERK pathway, which upregulates EGR-1 thereby suppressing the expression of TRAIL. Moreover, we provide evidence that APC can induce a cell signaling response through a PAR-1/S1P1-dependent but EPCR-independent mechanism.